Amplifying the Dalit Pentecostal Historical Narrative amid the Persistent Syrian Christian 'Privileged' Narrative in Kerala - Varghese Meloottu, Allan (Religions, 2023)
While studies indicate that Pentecostal teachings center the egalitarian move of the Holy Spirit with empowering effects on the social lives of the Dalits in the South Indian Pentecostal landscape, the persistence of ethnocentric behavior from “Syrian Christian” Pentecostals continues. Hence, this paper focuses on exploring the historical development of a Syrian Christian identity marker as a privileged one that became prefixed by the Pentecostals in Kerala, especially in Travancore. In this regard, this paper seeks to answer questions such as: How did caste dynamics structure the formation of Christian communities in Kerala? How did the historical Western missionary interactions deal with local caste-influenced distinctions (especially between the “Syrian Christian” and Dalit communities)? How did Pentecostalism challenge and perpetuate the Syrian Christian caste identity? Through an intersectional (religion and caste) historical analysis, this paper shows that the Syrian Christian community has been integrated into the caste system for the last two thousand years of Christian history in Kerala. At the same time, via a more inclusive historical narrative, the paper highlights Dalit conversions to Christianity since the sixteenth century as a critique against the privileged status of Syrian Christianity, even more so when Pentecostalism arrived at its shores, impacting the emergence of Dalit Pentecostalism.